Β Evaluate (π«π + ππ« + π)π = π βππ β ππππππ + πππ5
Β Let us solve the differential equation "(D^2 + 6D + 9)y = e^{\u22123t} \u2212 3\\cos 4t +\\log 5."
The characteristic equation "k^2+6k+9=0" is equivalent to "(k+3)^2=0," and hence has the roots "k_1=k_2=-3." It follows that the general solution is of the form "y=(C_1+C_2t)e^{-3t}+y_p,"
where "y_p=at^2e^{-3t}+b\\cos 4t+c\\sin 4t+d." Then "y'_p=2ate^{-3t}-3at^2e^{-3t}-4b\\sin 4t+4c\\cos 4t,\ny''_p=2ae^{-3t}-6ate^{-3t}-6ate^{-3t}+9at^2e^{-3t}-16b\\cos 4t-16c\\sin 4t."
We get the equation "2ae^{-3t}-6ate^{-3t}-6ate^{-3t}+9at^2e^{-3t}-16b\\cos 4t-16c\\sin 4t+6(2ate^{-3t}-3at^2e^{-3t}-4b\\sin 4t+4c\\cos 4t)+9(at^2e^{-3t}+b\\cos 4t+c\\sin 4t+d)=e^{-3t}-3\\cos 4t+\\log 5,"
which is equivalent to
"2ae^{-3t}+(-7b-24c)\\cos 4t+(-7c-24b)\\sin 4t+9d=e^{-3t}-3\\cos 4t+\\log 5."
We conlude that "2a=1,\\ -7b-24c=-3,\\ -7c-24b=0,\\ 9d=\\log 5." It follows that "a=\\frac{1}2,\\ d=\\frac{1}9\\log 5, c=-\\frac{24}7b,\\ 7b-\\frac{576}7b=3." Consequently, "a=\\frac{1}2,\\ d=\\frac{1}9\\log 5, \\ b=-\\frac{21}{527}, c=\\frac{72}{527}."
We conclude that the general solution of the differential equation "(D^2 + 6D + 9)y = e^{\u22123t} \u2212 3\\cos 4t +\\log 5" is
"y=(C_1+C_2t)e^{-3t}+\\frac{1}2t^2e^{-3t}-\\frac{21}{527}\\cos 4t+\\frac{72}{527}\\sin 4t+\\frac{1}9\\log 5."
Comments
Leave a comment